KAJIAN ESTETIKA PENERANGAN JALAN UMUM DI KAWASAN JALAN SENOPATI, JALAN SURYO, JALAN WOLTER MONGINSIDI, DAN JALAN GUNAWARMAN, JAKARTA SELATAN: AESTHETIC STUDY OF PUBLIC STREET LIGHTINGIN THE AREA OF ​​JALAN SENOPATI, JALAN SURYO,JALAN WOLTER MONGINSIDI, AND JALAN GUNAWARMAN, SOUTH JAKARTA - Awang Eka Novia Rizali; Ariani, Ariani; Jasfi, Elda Franzia; Damayanti , Resky Annisa; Ali, Raphael Jordan (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2024)
Street Lighting is a public facility that is used to improve road safety by lighting the road at night and helping road users to see the road they are on more clearly at night. The areas around Jalan Senopati, South Jakarta, are residential and commercial areas where people are busy carrying out their daily activities. These three road areas are equipped with pedestrians and supporting facilities in the form of revitalized street lighting. The objects of this research are street lighting located in the areas of Jalan Senopati, Jalan Suryo, Jalan Wolter Monginsidi, and Jalan Gunawarman, South Jakarta. The focus of the research problem is the various forms and aesthetic elements of street lighting in the areas of Jalan Senopati, Jalan Suryo, Jalan Wolter Monginsidi, and Jalan Gunawarman, South Jakarta, and how aesthetics are applied to street lighting ornaments in these areas. The research method used is descriptive qualitative, to identify and describe the application of aesthetics to street lighting ornaments in the areas of Jalan Senopati, Jalan Suryo, Jalan Wolter Monginsidi, and Jalan Gunawarman, South Jakarta. The results of this research are that there is a diversity of aesthetic elements used in street lighting, namely in the form of the development of geometric shapes, local wisdom cultural ornaments, and forms of narrative depiction of urban activities in the area. Application of ornamental aesthetics to areas and empty spaces that does not interfere with the functional purpose and benefits of the product as street lighting in the area.